Using Cloud Computing as an Infrastructure Case Study- Microsoft Azure - Qarkaxhija, Jusuf (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In recent years, the cloud has achieved an immense popularity in the world of tech. This has provided new and improved strategies for cost reduction, and for ensuring better utilisation of cloud resources. Implementation of this model is continuously increasing in numerous businesses , due to the many benefits that the companies are attaining. These cloud resources can belong to either, the infrastructure or platform model. A vast attention has been directed towards the virtualization technology, because the cloud is largely relied upon it. With the help of virtualization, one can quickly download apps or websites, from the cloud. In order to yield the full potential of the cloud, companies should migrate all their current applications to the cloud, and in order to do that- only an internet connection is required. Migration of the existing systems to a scalable cloud solution, can reduce hardware related costs , such as : servers, installation of operating system, database and licence system costs, deployment of database products , and finally employment of professional staff to develop and maintain the system. This research attempts to study and analyze Microsoft Azure, in particular the virtual machine - as part of its infrastructure. The main priority lies in establishing a secure cloud data storage system.